IDIOPATHIC TASTE IMPAIRMENT IN A YOUNG WOMAN: A CASE REPORT - Tenny Setiani Dewi; Nelly Nainggolan; Dewi Zakiawati (Dentino : Jurnal Kedokteran Gigi, 2022)
ABSTRACT  Background: The underlying cause of taste impairment includes damage in the central or peripheral nervous system, nutrition deficiency, systemic disease, or idiopathic. This condition usually occurs with advancing age. Taste alteration may affect the patient’s psychological aspect and causing malnutrition or even develop into more serious health problems. Purpose: This report aims to evaluate an unusual partial ageusia in a young woman and to review articles with idiopathic taste disorders. Case: A 33-year-old woman was referred to the Department of Oral Medicine from the neurology department with a primary diagnosis of migraine and median nerve mononeuropathy. The patient also complained of loss of tastes (salty, bitter, and sour) accompanied by numbness on the palate and left buccal mucosa for the past two weeks. Case Management: The patient was given a 0.12% chlorhexidine digluconate mouthwash and 25 mg zinc tablets twice a day. After 2 weeks, she can identify bitter, and followed by sweet and sour in the next few weeks, as well as improvement of the numbness. Eighteen studies of idiopathic taste disorders from 1991-2021 have been reported in the literature. Conclusion: Taste disorders with unknown aetiology may happen in young individuals. Zinc has been proven as a beneficial micronutrient to treat patients with idiopathic taste impairment. Dentists should consider this approach to resolve the symptoms and accelerate the healing process of possible co-occurrence systemic diseases.  Keywords: Ageusia, idiopathic, Taste dysfunction, Treatment